Does context matter in misophonia? A multi-method experimental investigation - Siepsiak, Marta; Vrana, Scott R.; Rynkiewicz, Andrzej; Rosenthal, M. Zachary; Dragan, Wojciech Łukasz (Frontiers in Neuroscience, 2023)
Misophonia is a recently defined disorder in which certain aversive repetitive sounds and associated stimuli elicit distressing and impairing affective, behavioral, and physiological responses.The responses in misophonia may be stronger when the sound is produced by close friends and family, suggesting that the context in which a triggering cue occurs may have an important role in misophonia. As such, the goal of this study was to test experimentally whether the context of the sound source influences affective and psychophysiological responses to triggering stimuli in misophonia. Sixty one adults with misophonia and 45 controls listened to audio recordings (8 seconds) of human eating, animals eating, and human mouth smacking sounds (without eating). After a break, the same audio recordings were presented embedded within videos of human eating (congruent stimuli), animals eating (congruent stimuli), and, in the mouth smacking condition, with visually incongruent stimuli (hands playing in mud or in a bowl with a watery dough). Psychophysiological responses - skin conductance response (SCR) and heart rate (HR), and self-reported affective responses (valence, arousal, dominance) were gathered during the experiment in a laboratory. Participants with misophonia assessed all the stimuli as more negative and arousing than the controls, and reported feeling less dominant with respect to the sounds. Animal and mouth smacking sounds were assessed by all the participants as less negative and arousing than human eating sounds, but only in the audio-video conditions. SCR data partially confirmed increased psychophysiological arousal in misophonia participants during an exposure to mouth sounds, but did not reflect the self-report changes in response to different contexts. Misophonia participants had deeper deceleration of HR than controls during human eating sound with congruent video stimuli, while there was no group difference during human mouth smacking with incongruent video stimuli. Results suggest that the context of mouth sounds influences affective experiences in adults with misophonia, but also in participants without misophonia. Presentation of animal eating sounds with congruent visual stimuli, or human mouth smacking sounds with incongruent stimuli, decreased self-report reaction to common misophonic triggers.